Enhancing Type 2 Diabetes Management: The Role of Pharmacist-Led Education and Booklets - Lusiana, Ika; Yosef Wijoyo (Community Medicine and Education Journal, 2024)
Type 2 diabetes mellitus (T2DM) is a global health concern, necessitating effective management to prevent complications. Pharmacists, as accessible healthcare professionals, can play a pivotal role in patient education and self-management support. This study aimed to evaluate the impact of pharmacist-led education and booklets on glycemic control and self-management behaviors in patients with T2DM. A quasi-experimental study was conducted at a hospital in Central Java, Indonesia. Patients diagnosed with T2DM for at least six months were recruited. The intervention group received pharmacist-led education and a booklet, while the control group received standard care. Fasting blood glucose (FBG) and self-management behaviors were assessed at baseline and after three months. The intervention group demonstrated a significant reduction in FBG levels compared to the control group (p < 0.05). Additionally, the intervention group showed improvements in self-management behaviors, including medication adherence, dietary control, and physical activity. Pharmacist-led education and booklets are effective in improving glycemic control and self-management behaviors in patients with T2DM. This intervention can be integrated into routine diabetes care to enhance patient outcomes.